376 Epidemiology of Immediate Type Adverse Drug Reactions and Rashes Elicited by Nsaid - Kinaciyan, Tamar (World Allergy Organization Journal, 2012)
BACKGROUND: NSAID are frequently used and can often cause adverse drug reactions (ADR) ranging from generally mild to sometimes severe and life-threatening reactions. ADRs are in most cases interpreted as pseudo-allergic, presumably non immunologic, but their dynamics and appearance in a subgroup of patients is suggestive for an IgE-mediated mechanism. METHODS: In this study, we retrospectively analysed data of 501 patients from our outpatient clinic population of the past 7 years with ADR to NSAID. Data was evaluated regarding the culprit drug or drugs, type and severity of reactions, age, gender, atopy, number of co-medication, co-morbidity and infections etc. as risk factors. Further, skin test and provocation test results were reviewed for their clinical relevance and reliability. RESULTS: Acetylsalicylic acid (ASA), paracetamol, diclofenac, mefenamic acid and propyphenazone were found as top five of causative drugs for ADR. The most common symptoms were angioedema, urticaria, pruritus, exanthema and dyspnea. ASA caused dyspnea, angioedema and urticaria in the majority of the cases. Diclofenac was found to be the most common culprit for severe anaphylactic reactions, followed by paracetamol and propyphenazone. Sixty percent of the NSAID reactors suffered from an atopic disease or had an atopic predisposition. There was a significant association between proven hypersensitivity reactions and reaction initiation after drug intake regarding the time interval. CONCLUSIONS: Our data suggest that -atopic predisposition is a risk factor for intolerance reaction to NSAID, -ASS accounts for non-immunologic, intolerance reactions, whereas severe anaphylactic reactions to diclofenac and/or propyphenazone seem to be IgE-mediated, -a shorter time interval between drug intake and appearance of symptoms is supportive for clinical relevance and could be an indicator for IgE-mediated ADR. Acknowledgements: FWF project L467-B05.